Body Dynamics and Movement of the Actor in Theatre Performance - Jwan Bhaldin Muhamad Raoof; Kifee Ahmad Abdulqadr (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
The body of actor mechanical property, and a system dynamic complex, and every part of his body allows movements of property spend with the nature of the joint one who made the motion, in order to transform the performing operations representative to the degree of conscious, to achieve complete performance, we should know that the body of the actor depends on the law the mechanical movement of the body of Representative, therefore must Representative look for any movement in his body so that he could ensure and achieve cooperation and harmony to reach the dynamics of the body that must presence in all parts of the body, when any movement of the body which must show all duties at the beginning and the end is the author of all this work achieved by relying on a set of biomechanic’s Etudes by(Meyerhold) innovative by strengthening the viability of the joints and control it by the traffic flow, which depends on the coordination and higher harmonic, so as to establish the rules of all the basic skills of the representative, until it becomes the body of responsive actor movements play, high flexibility.